ANALISIS PERHITUNGAN PENDINGINAN TRAFO MENGGUNAKAN ISOLATOR CAIR MINYAK SAWIT - Muhamad Mustangin (Institut Teknologi Sawit Indonesia (ITSI), 2021)
The transformer that functions to increase/decrease the voltage is heated due to the flow of electric current.The heat must be removed so as not to damage the winding. The heat dissipation method uses a liquid topropagate heat into the air. Currently, mineral oil is generally used, but to improve the environment and bemore sustainable, it can be replaced with palm oil (CPO). The heat transfer palm oil of the transformer canbe calculated. The heat propagates from the heat source through the paper to the CPO, then to the ironcasing of the transformer and then to the free air. In order for CPO to cool properly, CPO needs to be cooledusing forced air so that the heat transfer process is optimal. Based on the assumption of transformerparameters and CPO parameters such as heat capacity, conductivity, density, viscosity and others, it isobtained that the flow properties of CPO are laminar with Reynolds number of 293. Pradle number of 173.99and Prandtl number of 30, then the convection coefficient CPO heat is 509.4 W/m2.oC. Based on thetemperature in the coil of 80oC, the temperature calculation on the coil wrapping paper is 72oC, thetemperature on the inside wall of the casing is 54.17oC and the temperature on the outer wall of thetransformer or in the free air is 53.53oC so that it is still below the standard or acceptable. This shows that a5,000 Watt heat source with a transformer casing length and width of 0.5 meters and a total radiator pipelength of 10 meters can reduce heat in the transforme